Highlighting the Importance of Full-Cell Testing for High Performance Anode Materials Comprising Li Alloying Nanowires. Issue 13 (1st January 2019) - Geaney, Hugh; Bree, Gerard; Stokes, Killian; McCarthy, Kieran; Kennedy, Tadhg; Ryan, Kevin M.
Abstract : Herein, the electrochemical performance of directly grown Ge nanowire anodes in full-cell Li-ion configurations (using lithium cobalt oxide cathodes) are examined. The impacts of voltage window, anode/cathode balancing and anode preconditioning are assessed. The cells had a useable upper cutoff of 3.9 V, with a higher voltage cutoff of 4.2 V shown by SEM analysis to lead to Li plating on the anode surface. The rate performance of Ge NW anodes was shown to be boosted within full-cells compared to half-cells, meaning that existing studies may underestimate the rate performance of alloying mode anode materials if they are only based on half-cell investigations. The capacity retention of the full-cells is lower compared to equivalent half-cells due to progressive consumption of cyclable Li. This phenomenon is demonstrated using a parallel anode and cathode delithiation approach that could be extended to other full-cell systems. The findings stress the importance of testing promising anode materials within full-cell configurations, to identify specific capacity fade mechanisms that are not relevant to half-cells and aid the development of higher energy density storage systems.